Physicochemical, Microbiological and Sensory Characteristics of Using Different Probiotic Fermented Milk - Tonguc, I. Erdem; Kinik, Ozer; Kesenkas, Harun; Acu, Merve (Pakistan Journal of Nutrition, 2013)
The objectives of this study were to determine how fermented milk could be produced using different combinations of probiotic cultures and also to determine their physical, chemical, microbiological and organoleptic properties during storage. The results indicate that using probiotics with the standard yoghurt bacteria as adjunct culture had positive effects on the physical, chemical and microbiological properties of the products. Moreover the majority of the panelists in the sensory evaluation described the probiotic fermented milk samples as having better aroma/flavour. Furthermore, it was seen that acidity and durability of aroma/flavour until the end of the storage period was better than normal yoghurt drink.